mHealth apps for teleconsultation and telemonitoring: the new frontiers of telemedicine and the legal frameworks on medical devices and on the protection of personal data (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
mHealth apps developed for teleconsultation and telemonitoring include software that collect, store and exchange information on the health status of individuals to allow a remote medical examination and a remote monitoring of a patient suffering from a chronic disease. In recent years the phenomenon of mHealth apps has deeply been studied, but uncertainty remains. In the absence of a specific regime for telemedicine, this paper will reconstruct the applicable rules in the European Union and Italian legal systems and investigate whether such a mHealth app should be considered a medical device and what are the requirements deriving from the data protection framework.
Keywords: Telemedicine; mHealth app; medical device; personal data; design